Polybrominated Diphenyl Ethers (PBDEs) in Indoor Air: Levels and Exposure - S Hazrati; S Harrad (Tehran University of Medical Sciences, 2005)
PBDE levels in 26 different indoor microenvironments including 13 homes, 12 offices and a private car were investigated. A mean indoor air concentration of 143.8 pg/m3 was determined with the offices being more contaminated than residential homes. The most abundant congener was identified to be BDE 47 followed by #s 99, 100, and 28, respectively. ΣPBDE concentrations in indoor air were on average ~ 7 times higher than HiVol derived outdoor air levels providing a significant source of these compounds to outdoor ambient air. The average daily human inhalation exposure to PBDEs was estimated to be 4.3 ng/person with a maximum intake value of 21.8 ng/person.